Perjuangan yang tak terkalah / Asrol Hasan - Hasan, Asrol (Academy of Language Studies, Universiti Teknologi MARA, Kedah, 2024)
Proudly mentioned, the poems featured in this anthology are a testimony to the depth of feelings, spirits, and the tireless solidarity of the authors with the Palestinian people. Each poem written from the depth and breadth of the soul serves as a powerful reminder of the shared humanity that unites us all.